Global Dynamics of Certain Mix Monotone Difference Equation via Center Manifold Theory and Theory of Monotone Maps - Kulenović, Mustafa R.S.; Nurkanović, Mehmed; Nurkanović, Zehra (Sarajevo Journal of Mathematics, 2020)
We investigate the global dynamics of the following rational difference equation of second order \begin{equation*} x_{n+1}=\frac{Ax_{n}^{2}+Ex_{n-1}}{x_{n}^{2}+f},\quad n=0,1,… , \end{equation*} where the parameters $A$ and $E$ are positive real numbers and the initial conditions $x_{-1}$ and $x_{0}$ are arbitrary non-negative real numbers such that $x_{-1}+x_{0}>0$. The transition function associated with the right-hand side of this equation is always increasing in the second variable and can be either increasing or decreasing in the first variable depending on the parametric values. The unique feature of this equation is that the second iterate of the map associated with this transition function changes from strongly competitive to strongly cooperative. Our main tool for studying the global dynamics of this equation is the theory of monotone maps while the local stability is determined by using center manifold theory in the case of the nonhyperbolic equilibrium point.